Description of the pseudocryptic species Conticribra weissflogiopsis sp. nov. (Thalassiosirales, Bacillariophyta) isolated from brackish waters in Korea, based on its cingulum structure and molecular analysis - Park, Joon Sang; Lee, Jin Hwan (Phytotaxa, 2014)
We describe the new fultoportulate diatom species, Conticribra weissflogiopsis, isolated from brackish waters in Korea, based on morphological characters and molecular data. The new species is characterized by having areolae venation with internal (semi-) continuous cribra, a flat valve face, a single marginal rimoportula replacing a marginal fultoportula, a subcentral ring of the valve face fultoportulae, and a dextral pattern of cingulum structure. The overall valve structure of C. weissflogiopsis resembles that of C. weissflogii; however, the cingulum structure differs between the two species—C. weissflogiopsis has a dextral offset of band opening in the cingulum, whereas C. weissflogii has a sinistral offset. Phylogenetic analysis of the nuclear small subunit ribosomal DNA (SSU rDNA) revealed that C. weissflogiopsis is located in the Conticribra clade. Further, the pairwise genetic distance based on the SSU rDNA and the internal transcribed spacer 2 (ITS2) indicated that C. weissflogiopsis is a distinct Conticribra species. On the basis of the morphology and molecular phylogeny, we expand the hypothesis regarding the morphological evolution of Conticribra species.